Effect of Locally Produced Ready-to-Use Therapeutic Food on Children under Five Years with Severe Acute Malnutrition: A Systematic Review - Rimbawan, Rimbawan; Nasution, Zuraidah; Giriwono, Puspo Edi; Tamimi, Kharisma; Fadly, Khaerul; Noviana, Astrid (Jurnal Gizi dan Pangan, 2022)
This review assessed the effect of Ready-to-Use Therapeutic Food (RUTF) on children under five years with Severe Acute Malnutrition (SAM). The reviewed studies were obtained from six databases. Using the search strategy, 3,521 studies were selected. After title and abstract screening, 75 studies were obtained for further full article screening. The inclusion criteria were types of study (RCT, quasi-RCT, or crossover), participants (SAM children aged 6−60 months with no complications), interventions (locally produced RUTF and standard RUTF), and outcome measures (recovery rate, mortality rate, weight gain rate, height gain rate, length of stay, weight-for-age z score, height-for-age z score, weight-for-length z score, anemia status, blood iron status, serum albumin, plasma amino acid level, adverse effects and acceptability of RUTF). A total of 33 studies were included in this review. Nine out of twenty-two studies that used standard RUTF had positive effects on recovery outcomes in children with SAM. The alternative RUTF produced from local protein sources showed slightly lower positive effects on SAM treatment than those of standard RUTF. Since the studies used different methods to assess the outcome, no formula could be selected as the best formula and selection should be made based on individual research objectives. In conclusion, both standard and the alternative locally produced RUTF can be applied for treatment of SAM by considering the local preferences, ingredients availability, production sustainability and product safety.